Effectiveness of the School-Based Intervention Program on Leaners’ Literacy and Numeracy Skills Development as Perceived by Teachers - Trabado, Rossana (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of the School-Based Intervention Program on learners’ literacy and numeracy skills development in Milagros, Masbate, as perceived by teachers. Anchored on Bruner’s Constructivist Learning Theory, Vygotsky’s Social Constructivist Theory, and the Response to Intervention Framework of Fuchs and Fuchs, the study employed a quantitative descriptive-correlational research design. Using convenience sampling, the study surveyed 50 teacher-respondents through a researcher-made and expert-validated questionnaire using a four-point Likert scale. Data were analyzed using frequency count, percentage, weighted mean, ranking, and one-way ANOVA at the 0.05 level of significance. Findings showed that the School-Based Intervention Program was highly effective in improving learners’ literacy skills, particularly reading comprehension, vocabulary acquisition, writing skills, and fluency. It was also highly effective in strengthening numeracy skills, including basic computation, problem-solving, number sense, and application of mathematical concepts. The overall program was rated highly effective in terms of implementation and delivery, appropriateness of strategies and materials, monitoring and evaluation, and impact on learners’ academic improvement. The ANOVA result showed no significant difference in teachers’ perceptions based on demographic profile, as the computed F-value of 0.706 was lower than the critical F-value of 2.579 and the p-value of 0.592 was greater than 0.05. The study concluded that the program effectively supports learners’ academic growth and recommended sustained school support, improved instructional materials, regular monitoring, professional development, and stronger focus on higher-order literacy skills and contextualized numeracy activities. The study supports SDG 4, Quality Education, and SDG 17, Partnerships for the Goals, by promoting foundational learning and collaboration among teachers, school leaders, administrators, parents, and education stakeholders. Its sustainability impact lies in strengthening educational, institutional, professional, and community support systems for literacy and numeracy development.